Surgical re‐excision vs. observation for histologically dysplastic naevi: a systematic review of associated clinical outcomes. (1st September 2018) - Vuong, K.T.; Walker, J.; Powell, H.B.; Thomas, N.E.; Jonas, D.E.; Adamson, A.S.
Summary: Background: The management of histologically dysplastic naevi (HDN) with re‐excision vs. observation remains controversial because of lack of evidence about associated melanoma outcomes. Objectives: To assess published data on the development of biopsy‐site primary cutaneous melanoma among biopsy‐proven HDN managed with either re‐excision or observation. Methods: A systematic review of all published data: a total of 5293 records were screened, 18 articles were assessed in full text and 12 studies met inclusion criteria. No controlled trials were identified. Results: Most studies (11 of 12, 92%) were retrospective chart reviews, and one was both a cross‐sectional and cohort study. Many studies (nine of 12, 75%) had no head‐to‐head comparison groups and either only reported HDN that were re‐excised or observed. A total of 2673 (1535 observed vs. 1138 re‐excised) HDN of various grades were included. Follow‐up varied between 2 weeks and 30 years. Nine studies reported that no melanomas developed. Eleven biopsy‐site melanomas developed across three of the studies, six among observed lesions (0·39%) and five among re‐excised lesions (0·44%). Conclusions: Based upon the available evidence the rates of biopsy‐site primary melanoma were similarly low among observed lesions and re‐excised lesions. This suggests that HDNs can be observed with minimal adverse melanoma‐associated outcomes. However, all included articles were of low quality and further prospective trials could better guide clinical decision making.